Wideband Circularly Polarized Sequentially-Rotated Cubic-Shaped Dielectric Resonator Array Antenna - Supreeyatitikul, Nathapat; Lertwiriyaprapa, Titipong; Phongcharoenpanich, Chuwong; Konpang, Jessada (My University, 2025)
This study proposes a cubic-shaped dielectric resonator (DR) broadband circularly polarized (CP) array antenna for S-band networks. The design includes 2 × 2 cubic-shaped DR units and a substrate. The upper and lower substrates feature a split-annular aperture ground plane and a sequential-phase feed. Employing the sequential-phase feed, the proposed array antenna aims to enhance performance metrics, including RLBW, ARBW, and antenna gain. Simulation results indicate a RLBW of 56.25% (2.25 - 3.6 GHz) and an ARBW of 43.33% (2.38 - 3.42 GHz). The optimal gain achieved is 9.14 dBic at 3.3 GHz. Furthermore, the array antenna demonstrates right-hand circular polarization (RHCP) characteristics, rendering it suitable for S-band technology.
Keywords: Axial ratio bandwidth; circularly polarized antenna; dielectric resonator; RHCP; sequential-phase feed